Relatório de viagem ao exterior [Madrid, Espanha] - ROCHA NETO, Manoel Barretto (2010)
Seabed: New Frontier - Exploration and Exploitation of Deep Seabed Mineral Resources in the Area: Challenges for the International Community, and Opportunities for Collaborative Research